Table of Integrals - Forms Involving `ax^2+bx+c`

The integrals below involve `ax^2+bx+c`

1) `int  1/(ax^2+bx+c)  dx = 2/sqrt(4ac-b^2) tan^-1 ((2ax+b)/sqrt(4ac-b^2))`

                           OR `= 1/sqrt(b^2-4ac)  ln  ((2ax+b-sqrt(b^2-4ac))/(2ax+b+sqrt(b^2-4ac)))`

If `b^2=4ac`, then `ax^2+bx+c=a(x+b/(2a))^2`; use the results in the tables for Integrals Involving `ax+b`.

If `b=0`, use the results in the table for Integrals Involving `x^2+a^2`.

If `a` or `c=0`, use the results in the tables for Integrals Involving `ax+b`.

2) `int  x/(ax^2+bx+c)  dx = 1/(2a)  ln  (ax^2+bx+c)-b/(2a)  int  1/(ax^2+bx+c)  dx`

3) `int  x^2/(ax^2+bx+c)  dx = x/a-b/(2a^2)  ln  (ax^2+bx+c)+(b^2-2ac)/(2a^2)  int  1/(ax^2+bx+c)  dx`

4) `int  x^m/(ax^2+bx+c)  dx = x^(m-1)/((m-1)a)-c/a  int  x^(m-2)/(ax^2+bx+c)  dx  -b/a  int  x^(m-1)/(ax^2+bx+c)  dx`

5) `int  1/(x(ax^2+bx+c))  dx = 1/(2c)  ln  (x^2/(ax^2+bx+c))-b/(2c)  int  1/(ax^2+bx+c)  dx`

6) `int  1/(x^2(ax^2+bx+c))  dx = b/(2c^2)  ln  ((ax^2+bx+c)/x^2)-1/(cx)+(b^2-2ac)/(2c^2)  int  1/(ax^2+bx+c)  dx`

7) `int  1/(x^n(ax^2+bx+c))  dx = -1/((n-1)cx^(n-1))-b/c  int  1/(x^(n-1)(ax^2+bx+c))  dx-a/c  int  1/(x^(n-2)(ax^2+bx+c))  dx`

8) `int  1/(ax^2+bx+c)^2  dx = (2ax+b)/((4ac-b^2)(ax^2+bx+c))+(2a)/(4ac-b^2)  int  1/(ax^2+bx+c)  dx`

9) `int  x/(ax^2+bx+c)^2  dx = -(bx+2c)/((4ac-b^2)(ax^2+bx+c))-b/(4ac-b^2)  int  1/(ax^2+bx+c)  dx`

10) `int  x^2/(ax^2+bx+c)^2  dx = ((b^2-2ac)x+bc)/(a(4ac-b^2)(ax^2+bx+c))+(2c)/(4ac-b^2)  int  1/(ax^2+bx+c)  dx`

11) `int  x^m/(ax^2+bx+c)^n  dx = -x^(m-1)/((2n-m-1)a(ax^2+bx+c)^(n-1))+((m-1)c)/((2n-m-1)a)  int  x^(m-2)/(ax^2+bx+c)^n  dx -((n-m)b)/((2n-m-1)a)  int  x^(m-1)/(ax^2+bx+c)^n  dx`

12) `int  x^(2n-1)/(ax^2+bx+c)^n  dx = 1/a  int  x^(2n-3)/(ax^2+bx+c)^(n-1)  dx-c/a  int  x^(2n-3)/(ax^2+bx+c)^n  dx  -b/a  int x^(2n-2)/(ax^2+bx+c)^n  dx`

13) `int  1/(x(ax^2+bx+c)^2)  dx = 1/(2c(ax^2+bx+c))-b/(2c)  int  1/(ax^2+bx+c)^2  dx+1/c  int  1/(x(ax^2+bx+c))  dx`

14) `int  1/(x^2(ax^2+bx+c)^2)  dx = -1/(cx(ax^2+bx+c))-(3a)/c  int  1/(ax^2+bx+c)^2  dx -(2b)/c  int  1/(x(ax^2+bx+c)^2)  dx`

15) `int  1/(x^m(ax^2+bx+c)^n)  dx = -1/((m-1)cx^(m-1)(ax^2+bx+c)^(n-1))-((m+2n-3)a)/((m-1)c)  int  1/(x^(m-2)(ax^2+bx+c)^n)  dx -((m+n-2)b)/((m-1)c)  int 1/(x^(m-1)(ax^2+bx+c)^n)  dx`